Partisipasi Masyarakat Dalam Program Kampung Iklim (Proklim) Studi Pada RW12 Kelurahan Umbansari Kota Pekanbaru - Elly Nielwaty; Fara Meriansari; Hermanto Hermanto (Indra Institute Research & Publication, 2023)
This Article relates to how community participation in the Climate Village Program (Proklim) in RW12 Umbansari Village, Pekanbaru City. The phenomenon found in this Proklim research is the low level of community participation in coping and adaptation action activities as well as the institutions in RW12 according to the achievements that have been achieved based on the results of the proklim target assessment, and the lack of outreach to the community about Proklim activities so that people are not aware what are the goals and objectives of the proklim. This study aims to determine the level of community participation in proklim activities, as well as to find out what are the inhibiting factors that make community participation still not achieved in proklim in RW12 Umbansari Village. The theory used in this study is T.Ndraha's theory of participation in the process of decision making, implementation, use of results and evaluation. This study used a qualitative research method, namely by taking a phenomenological approach and collecting data using interview techniques, direct observation and documentation. The results of this study are that the target has not been achieved according to proklim standardization due to the lack of community participation in Proklim in RW12 Umbansari Village, due to low socialization, low public awareness, apathetic people, and community work factors that hinder the level of community participation in Proklim